THE DEFINITIVE CONSTITUTION OF TAX CREDIT AND THE PRESCRIPTION TERM (Reflection and Critique Law Magazine, 2022)
The present work aims to analyze how and at what moment the constitution of the tax credit and its definitive constitution occurs, pointing, then, the origin of the statute of limitations, as well as its causes of interruption and suspension. For this purpose, it intends to make considerations about the taxable event, the tax obligation and the tax posting, discussing their modalities and the particularities of each one about the moment of the constitution of the tax credit and the beginning of the statute of limitations. Based on the doctrine legislation, and jurisprudence of the Superior Courts, it aims to outline a coherent legal reasoning on the subject.